Detection of Toxic Compounds in Water with an Array of Optical Reporters. (2015) - Branchini, C. Guanais; Dini, F.; Lundström, I.; Paolesse, R.; Di Natale, C.
Abstract: An opto-electronic tongue, prepared using porphyrins, pH indicators, and their mixtures, has been tested for the analysis of toxic compounds in potable water. The color changes of sensitive dyes immersed in a water solution containing the target analytes were measured with an optical platform made by four LEDs (as light sources) and a digital camera (detector). We demonstrate that blends of dyes might be endowed with sensing properties wider than those of the single constituents, enabling the identification of a range of toxic compounds at concentrations smaller than 10 -6 mol/L. Furthermore, the use of the reporters in a sensor array configuration allows for the identification of the compounds disregarding their concentration.